Comprehensive safety assessment of two-well-horizontal caverns with sediment space for compressed air energy storage in low-grade salt rocks - Li, Qihang; Liu, Wei; Jiang, Liangliang; Qin, Jianxu; Wang, Yifan; Wan, Jifang; Zhu, Xuanshi (Journal of energy storage, 2024)
To expedite the construction and implementation of compressed air energy storage (CAES) in under- ground salt caverns (USCs), conducting a thorough stability assessment is crucial to ensure the safe operation of underground salt cavern gas storage (SCGS). Herein we present a theoretical model for the volumetric inversion of two-well-horizontal (TWH) caverns, based on salt extraction, salt layer characteristics, and interlayer ratio, using data from a low-grade salt mine in Feicheng City, China. In addition, we simulated the volume loss rate (VLR), displacement, and plastic zone volume (PZV) for various levels of high sediment content (SC) (50 %, 60 %, 70 %, 80 %, 90 %) and internal air pressure (IAP) (8.1 MPa, 9.45 MPa, 21.6 MPa) in the roof, waist, and connected areas of both high and low caverns within the TWH-cavern. The results reveal that the creep characteristics of the high cavern are more pronounced, and the combined effects of SC and IAP effectively limit roof deformation. How- ever, the displacement of the high cavern waist increases by 0.028 m (IAP = 8.1 MPa) and 0.006 m (IAP = 21.6 MPa) as SC rises from 80 % to 90 %. In the connected area, displacement values increase from 0.634 m to 0.852 m (IAP = 8.1 MPa) as SC increases from 50 % to 90 %. These findings emphasize that the sediment surface is a criterion for measuring whether the increase in SC inhibits or promotes cavern deformation. The cavern roof remains the most critical component for ensuring the safe operation of SC-CAES. Therefore, this study provides a theoretical basis for evaluating the safety of TWH-cavern energy storage in low-grade salt rock reservoirs and expands the potential sites for SC-CAES.